Challenges in the treatment of small cell lung cancer in the era of immunotherapy and molecular classification. (January 2023) - Caliman, Enrico; Fancelli, Sara; Petroni, Giulia; Gatta Michelet, Marta Rita; Cosso, Federica; Ottanelli, Carlotta; Mazzoni, Francesca; Voltolini, Luca; Pillozzi, Serena; Antonuzzo, Lorenzo
Highlights: Current therapeutic strategies for SCLC remain limited. Immune checkpoint inhibitors set a new benchmark for the treatment of SCLC. Pro-immunogenic or immunosuppressive features of TME modulate sensitivity to ICIs. Molecular classification of SCLC has opened a new scenario for new treatment options. Each molecular subtype of SCLC may present specific therapeutic vulnerabilities. Abstract: For many years the standard of care for small cell lung cancer (SCLC) has remained unchanged. Despite decades of active research, current treatment options are limited and the prognosis of patients with extended disease (ED) SCLC remains poor. The introduction of immune checkpoint inhibitors (ICIs) represents an exception and the only recent approval for ED-SCLC. However, the magnitude of benefit obtained with immunotherapy in SCLC is much more modest than that observed in other malignancies. Different pro-immunogenic or immunosuppressive features within the tumor microenvironment of SCLC may either modulate the sensitivity to immunotherapy or conversely dampen the efficacy of ICIs. Beside immunotherapy, a deeper understanding of the molecular biology of SCLC has led to the identification of new therapeutic targets for this lethal malignancy. Recent epigenetic and gene expression studies have resulted into a new molecular classification of four distinct subtypes of SCLC, defined by the relative expression of key transcription regulators and each characterized by specific therapeutic vulnerabilities. This review discusses the rationale for immunotherapy in SCLC and summarizes the main ICIs-trials in this tumor. We provide also an overview of new potential therapeutic opportunities and their integration with the new molecular classification of SCLC.